ON POSITIVE AND NEGATIVE IONOSPHERIC STORMS - Chukwuma V.U. (My University, 2007)
A study is made of the intense storms of March 13-15, 1989 (Dst = -600nT), October 20-21, 1989 (Dst = -266 nT) and April 1-2, 1973 (Dst = -211 nT) in regards to the appearance of positive storm before the beginning of a geomagnetic disturbance in the mid-latitudes and the occurrence of strong negative phase at the equator. F2 region global structure response to the geomagnetic storms was studied using foF2 data obtained during the storms from a global network of ionosonde stations. Investigated phenomena were only observed, on October 20, 1989, in only three of the nineteen plots representing ~16% occurrence for the case study of March and October 1989 storms: the positive storms at Slough (54.4°N) and Uppsala (59.86°N) and a negative storm at Ouagadougou (12.4°N). These ionospheric storms were caused by the southward turning of Bz at ~2100 UT on October 18 which got to a change in Bz of δBz = 12.2 nT at 2300 UT on October 18. In the case of the storm of April 1-2, 1973, the phenomena had ~69% occurrence: the positive storms at Wakkanai (45.4°N), Akita (39.7°N), Kokubunji (35.7°N), Kiev (50.5°N) Sofia(42.7°N), Ottawa (45.4°N), Boulder (40.0°N) and Point Arguello (35.6°N) and a negative storm at Manila (14.7°N). These ionospheric storms appear to be caused by the southward turning of Bz at ~1500 UT which got to a change in Bz of δBz = 13.6 nT at 1900 UT on March 31. The non explanation of these phenomena before now is because in the studies of ionospheric storms it is assumed that the beginning of any particular disturbance is defined by the onset of the magnetic storm. The use of sudden storm commencement (SSC) and main phase onset (MPO) for fixing the beginning of magnetic and ionospheric storms is fraught with problems that render a determination of the exact onset time difficult. The notion of onset of the magnetic storm as a prevailing idea restricted the geoeffectiveness of the solar wind to post onset time thereby foreclosing the explanation of any aspect of the morphology of ionospheric storms whose origin precede the onset reference time. © 2007 Akadémiai Kiadó, Budapest.
Keywords: D(FOF2) MAXIMUM; GEOMAGNETIC STORM; IONOSPHERIC F2 REGION; MAIN PHASE ONSET (MPO); MORPHOLOGY; SUDDEN STORM COMMENCEMENT (SSC)